Corporate Governance and Fraudulent Financial Reporting: The Role of Independence Figure - Jesslyn; Siti Khairani (eCo-Fin, 2025)
The main goal of this research is to analyze how corporate governance disclosure, focusing on the principle of independence, which includes the composition of the independent board of commissioners (BOD_IN), the effectiveness of the audit committee (ACE), the effectiveness of internal audit (IAE), and the quality of external auditors (EAQ) can affect fraudulent financial reporting (FFR). This research uses Beneish M-Score model to determine the indication of FFR, then analyze it with logistic regression analysis, performed and processed with IBM SPSS Statistics 26 software.  The data is collected from annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2022-2023. The final number of samples used in this study are 57 companies for two years which were taken by purposive sampling. The result of this research shows that all variables did not have a significant effect on fraudulent financial reporting. In conclusion, independence fugure on corporate governance did not have any significant influence on fraudulent financial reporting.